Mathematics

Question

When adding negative and positive numbers, you can use the associative and commutative properties to group all of the positive addends and then group all the negative addends. Which expression shows the second step of this method?

5 + (-1) + (-5) + (-2) + 11 + (-7) + 2

1 Answer

  • Answer:

    The second step of this method is

    [tex]5+(-1)+(-5)+(-2)+11+(-7)+2=(5+11+2)-(1+5+2+7)[/tex]

    The value of the given expression is

    [tex]5+(-1)+(-5)+(-2)+11+(-7)+2=3[/tex]

    Step-by-step explanation:

    Given expression is [tex]5+(-1)+(-5)+(-2)+11+(-7)+2[/tex]

    To find the value of the given expression  [tex]5+(-1)+(-5)+(-2)+11+(-7)+2[/tex]:

    Arranging positive and negative addends  by using the associative and commutative properties of the given expression as below:

    [tex]5+(-1)+(-5)+(-2)+11+(-7)+2=5+11+2+(-1)+(-5)+(-2)+(-7)[/tex]

    [tex]=(5+11+2)-(1+5+2+7)[/tex]

    [tex]=18-15[/tex]

    [tex]=3[/tex]

    [tex]5+(-1)+(-5)+(-2)+11+(-7)+2=3[/tex]

    The second step of this method is

    [tex]5+(-1)+(-5)+(-2)+11+(-7)+2=(5+11+2)-(1+5+2+7)[/tex]

    The value of the given expression is

    [tex]5+(-1)+(-5)+(-2)+11+(-7)+2=3[/tex]

NEWS TODAY